Preparing school leader to lead ICT - rich schools of 21st century: C+++ Framework - Mustafayev, Ramil (2015)
Abstract Background: Despite considerable investment in ICTs in schools around the world the new innovations have not had the anticipated effect on education. In many schools the world over ICT implementation does not transpass the basic infrastructure acquisition stage. While the factors affecting the successful integration of ICTs in schools are a myriad, the literature particularly emphasizes the role of leadership. With the global push for digitalization in education as well as in virtually all spheres of life, and its follow-ups at local school level, educational leaders are left with a lot to ponder about. While it has been well recorded in the literature and research agendas that leaders can’t be left on their own, and that they need to be well-prepared before and while they execute their duties as school heads, the leadership of the claimed recent transformation of education fails to be supported likewise. Aim: This study was carried out in order to formulate a framework that could help school heads with professional development, whether formal or informal, in the field of information and communication technologies (ICTs) leadership in schools. The aim was not to advocate the use of technology in education as is the case in many research papers on ICT and educational leadership, but to help educational leaders to obtain a balanced stance on ICTs. It aimed for an informed stance that is free from the vicious power struggles, marketization of education and false promises on the one hand, and ignorant dismissal of the potential benefits of technologies on the other. In other words, the aim was to help those aspiring and already sitting school heads to be able to prepare themselves for ‘purpose driven’ ICT implementation for education. Method: The study involved three sources of data gathering. In an interdisciplinary study the initially developed framework took its origins in the existing literature on ICT leadership in schools worldwide and five expert interviews. Two of the experts came from the side of educational technology and other two from leadership studies while one had a background in both. The resultant framework was tested in a needs assessment through surveys and focus group interviews with participants of a leadership preparation programme in a UK university. Results: The outcome of the study was the formulation of a framework called C+++ with four domains covering four aspects of ICT leadership under Convenience, Competence, Confidence and Commitment. Initial assessment showed that such a framework is required by those interested in school headship. First two of the four hierarchical domains were found to be a better fit for National College provided leadership preparation programmes. The latter two domains are suitable for research intensive university leadership studies. Conclusion: C+++ framework is at its early stage of development and there is need for further validation and refinement of the framework. Also there is a need to validate the framework in action. Key words: ICTs, educational technology, school leadership, theoretical framework, needs assessment, expert interviews.